Capturing the Shadow and Light of Researcher Positionality: A Picture-Prompted Poly-Ethnography. (8th December 2020) - Kassan, Anusha; Nutter, Sarah; Green, Amy R.; Arthur, Nancy; Russell-Mayhew, Shelly; Sesma-Vasquez, Monica
Acknowledging researcher positionality and engaging in ongoing reflexivity are important components of qualitative research. In this manuscript, we share our experiences of examining our positionality and engaging in reflexive practice related to a research project with newcomer women in Canada. As a team of researchers from diverse backgrounds, we engaged in a picture-prompted poly-ethnographic conversation to better understand our attitudes, assumptions, and biases in relation to the topic of our research and gain a better understanding of what were asking of participants. Using thematic analysis, we uncovered four themes: 1) researchers bring multiple identities, 2) researchers bring privilege/power, 3) understanding what we call home, and 4) walking in participants' shoes. We discuss these themes in detail, highlighting their implications for reflexive research with newcomer communities.